Anaplastic lymphoma kinase (ALK) and c-ros oncogene 1 (Rosi) genes on lung cancer samples of Iraqi patients - Talib Abdallah, Mays; Khalaf Al-Fahdawi, Mahmoud H.; Joodi Al Janabi, Zaid Mohammed; Essam Abdulmuttaleb, Mohammed; Zuhair Alsammarraie, Ahmed; Jabbar Dawood , Noor; Kadhom, Mohammed (Journal of Neonatal Surgery, 2025)
Lung cancer, a global disease, is classified into two main categories: non-small cell lung cancer (NSCLC) and small cell lung cancer (SCLC). NSCLC is accounted for 85% of all lung cancer diagnoses and is divided into three subgroups: squamous cell carcinoma, adenocarcinoma, and large cell carcinoma. The most common type is adenocarcinoma which occurs most commonly in non-smokers, and more frequently in females than males. Both genetics and environmental factors play a role in the development of lung cancer. The anaplastic lymphoma kinase (ALK) gene located on chromosome 2 is a key regulator of cell proliferation and signal transduction. In addition to anaplastic large-cell lymphoma (ALCL), ALK gene alterations were initially associated with this malignancy, mutations, and fusions; they have now also been implicated in other malignancies, including non-small cell lung cancer (NSCLC). The way how signaling and differentiation in cells, like neuronal ones, happens also depends on the ROS1 gene located on chromosome 6q22.1. Other ROS1 alterations such as the ROS1-ALK fusion have also been implicated in the progression of NSCLC. Employing cutting-edge molecular techniques such as targeted RNA sequencing and real-time PCR this study aimed to detect ALK and ROS1 gene fusions in non-small cell lung cancer patients. Our findings indicate that these genetic alterations play a significant role in patients' health and may serve as targets for therapies, particularly TKIs. The study accentuates the advantages of molecular diagnostic methods such as RT-PCR over traditional methods such as fluorescence in situ hybridization (FISH) based on their sensitivity, cost efficiency, and throughput.